1998
DOI: 10.1080/10420159808225768
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ag-doped Sb1.5Bi0.5Te3single crystals

Abstract: Single crystals of Sbl.5Bi0.5Te3 doped with Ag atoms ( c A~= 0-3.5 x 10'9atoms/cm3) were characterized by X-ray diffraction, measurement of reflectance in the plasma resonance frequency region, Hall coefficient, electrical conductivity, Seebeck coefficient and the figure of merit. It was found that Ag atoms in the crystal structure of Sbl sBio,5Te3 behave like acceptors; up to the concentration of c~g 1.7 x loL9 atoms/cm3 they increase the hole concentration, whereas in the concentration region of C A~ (1.7-3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Among few known ptype dopants, Ag is one of the most widely used elements. Losť'áet al 11 reported that Ag doping can increase the hole concentration due to the formation of negatively charged defects such as Ag Sb ″ or Ag Sb ′ . Recently, various methods, including melting constituent elements, 12 and ball-milling with subsequent thermal decomposition, 13 have been used to dope a small amount of Ag into BST.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Among few known ptype dopants, Ag is one of the most widely used elements. Losť'áet al 11 reported that Ag doping can increase the hole concentration due to the formation of negatively charged defects such as Ag Sb ″ or Ag Sb ′ . Recently, various methods, including melting constituent elements, 12 and ball-milling with subsequent thermal decomposition, 13 have been used to dope a small amount of Ag into BST.…”
mentioning
confidence: 99%
“…It should be noted that the atomic radius of Ag is a smaller than that of Sb or Bi (r Ag = 0.144 nm, r Sb = 0.159 nm, and r Bi = 0.170 nm). Thus, it can be concluded that Ag can diffuse into BST matrix during the SPS process and Ag can substitute for Sb 11 or Bi 17 considering if the fine Ag particles can be molten (T m ≈ 623 K 18 ) at 673 K.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al reported that ρ and α decreased with Ag, which substituted for Bi or Sb in p-type (Bi,Sb) 2 Te 3 [17]. The substitution of Ag for Bi or Sb was also reported by Klichová et al [18]. All of these results said that the Ag acted as an acceptor in the p-type (Bi,Sb) 2 Te 3 compounds.…”
Section: Introductionmentioning
confidence: 58%
“…18 Trends in the lattice parameter have also been investigated for Ag doping in BST. In previous studies, [8][9] the cell volume decreased at higher Ag concentrations due to the smaller size of Ag when compared to Bi or Sb. However, almost no variation in the cell volume was observed for the samples in this work (Table S1).…”
Section: Resultsmentioning
confidence: 97%